Child Care & Development - Minett, P. M. (London : Hodder Arnold, 2005)
This textbook has been updated to reflect changes to qualification specifications, as well as providing current practice. Each chapter includes activities to develop the key skills of communication, application of numbers and IT.
Previous ed.: London: John Murray, 2001.
Includes index.
Keywords: Child care; Children -- Health and hygiene; Child development; Child Care